Open geodata to support agricultural research. - DRUCKER, D. P. (2017)
We describe our effort on building a Spatial Data Infrastructure (SDI) at Embrapa, the Brazilian Agricultural Research Corporation, a networked public company composed by 46 research centers distributed throughout the country.